Synthesis and characterization of CdSe nanoparticles via thermal treatment technique - Salem, Aeshah; Saion, Elias; Al-Hada, Naif Mohammed; Kamari, Halimah Mohamed; Shaari, Abdul H.; Abdullah, Che Azurahanim Che; Radiman, Shahidan (Elsevier, 2017)
The synthesis of CdSe nanoparticles was undertaken via the thermal treatment method at varying calcination temperatures from 450 to 700 °C in alternate oxygen and nitrogen environment. Selenium powder was dissolved in ethylenediamine at 200 °C for 2 h before mixing with the metal precursor, cadmium nitrate and the capping agent polyvinylpyrrolidone to materialize the CdSe nanoparticles upon calcination. A series of measurements were employed to analyze the structural, elemental and optical properties of the attained nanoparticles at room temperatures using FTIR, XRD, EDX, SEM and TEM spectroscopies. XRD patterns and FTIR spectra revealed of the fact that, prior to calcination, an amorphous phase of the unheated material has taken shape, which after calcination achieved the crystalline structure of CdSe nanoparticles. The CdSe nanoparticle samples confirmed to be pure cadmium and selenium through EDX and FTIR analyses. The TEM images showed that as the calcination temperature raised from 450 to 700 °C the average particle size increased from 11 to 32 nm and the optical band gap energy decreased from 2.36 to 1.80 eV.